“Rogue” neutrophil-subset [DEspR+CD11b+/CD66b+] immunotype is an actionable therapeutic target for neutrophilic inflammation-mediated tissue injury – studies in human, macaque and rat LPS-inflammation models - Carstensen, Saskia; Müller, Meike; Tan, Glaiza L. A.; Pasion, Khristine Amber; Hohlfeld, Jens M.; Herrera, Victoria L. M.; Ruiz-Opazo, Nelson (Frontiers in Immunology, 2022)
Background and objective: The correlation (Rs > 0.7) of neutrophils expressing the dual endothelin1/signal peptide receptor (DEspR+CD11b+/CD66b+) with severity of hypoxemia (SF-ratio) and multi-organ failure (SOFA-score) in patients with acute respiratory distress syndrome (ARDS) suggest the hypothesis that the DEspR+ neutrophil-subset is an actionable therapeutic target in ARDS. To test this hypothesis, we conducted in vivo studies to validate DEspR+ neutrophil-subset as therapeutic target and test efficacy of DEspR-inhibition in acute neutrophilic hyperinflammation models. Methods: We performed tests in lipopolysaccharide (LPS)-induced acute neutrophilic inflammation in three species – human, rhesus macaque, rat – with increasing dose-dependent severity. We measured DEspR+CD66b+ neutrophils in bronchoalveolar lavage fluid (BALF) in healthy volunteers (HVs) 24-hours after segmental LPS-challenge by ChipCytometry, and DEspR+CD11b+ neutrophils in whole blood and BALF in an LPS-induced transient acute lung injury (ALI) model in macaques. We determined anti-DEspR antibody efficacy in vivo in LPS-ALI macaque model and in high-mortality LPS-induced encephalopathy in hypertensive rats. Results: ChipCytometry detected increased BALF total neutrophil and DEspR+CD66b+ neutrophil counts after segmental LPS-challenge compared to baseline (P =0.034), as well as increased peripheral neutrophil counts and neutrophil-lymphocyte ratio (NLR) compared to pre-LPS level (P <0.05). In the LPS-ALI macaque model, flow cytometry detected increased DEspR+ and DEspR[-] neutrophils in BALF, which was associated with moderate-severe hypoxemia. After determining pharmacokinetics of single-dose anti-DEspR[hu6g8] antibody, one-time pre-LPS anti-DEspR treatment reduced hypoxemia (P =0.03) and neutrophil influx into BALF (P =0.0001) in LPS-ALI vs vehicle mock-treated LPS-ALI macaques. Ex vivo live cell imaging of macaque neutrophils detected greater “intrinsic adhesion to hard-surface” in DEspR+ vs DEspR[-] neutrophils (P <0.001). Anti-DEspR[hu6g8] antibody abrogated intrinsic high adhesion in DEspR+ neutrophils, but not in DEspR[-] neutrophils (P <0.001). In the LPS-encephalopathy rat model, anti-DEspR[10a3] antibody treatment increased median survival (P =0.0007) and exhibited brain target engagement and bioeffects. Conclusion: Detection of increased DEspR+ neutrophil-subset in human BALF after segmental LPS-challenge supports the correlation of circulating DEspR+ neutrophil counts with severity measure (SOFA-score) in ARDS. Efficacy and safety of targeted inhibition of DEspR+CD11b+ neutrophil-subset in LPS-induced transient-ALI and high-mortality encephalopathy models identify a potential therapeutic target for neutrophil-mediated secondary tissue injury.